Interrogating the Evolutionary Paradox of Schizophrenia: A Novel Framework and Evidence Supporting Recent Negative Selection of Schizophrenia Risk Alleles - Liu, Chenxing; Everall, Ian; Pantelis, Christos; Bousman, Chad (Frontiers in Genetics, 2019)
Schizophrenia is a psychiatric disorder with a worldwide prevalence of 1%. The high heritability and reduced fertility among schizophrenia patients have raised an evolutionary paradox: why has negative selection not eliminated schizophrenia associated alleles during the evolution process? To address this question, we examined evolutionary markers, known as modern-human-specific sites and archaic-human-specific sites, using existing genome-wide association study data from 34,241 individuals with schizophrenia and 45,604 healthy controls included in the Psychiatric Genomics Consortium. By testing the distribution of schizophrenia single nucleotide polymorphisms (SNPs) with risk and protective effects in the human-specific sites, we observed a negative selection of risk alleles for schizophrenia in modern humans relative to archaic humans (e.g., Neanderthal and Denisovans). Such findings indicate that risk alleles of schizophrenia have been gradually removed from the modern human genome due to negative selection pressure. This novel evidence contributes to our understanding of the genetic origins of schizophrenia.